2017
DOI: 10.3390/f8080292
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Coarse Woody Debris on Microbial and Soil Properties in Pinus densiflora Sieb. et Zucc. Forests

Abstract: Abstract:Although coarse woody debris (CWD) is important for soil functioning, the mechanism which affects soil properties beneath CWD are unclear. Here, initial changes in microbial and soil properties were studied using homogenous CWD samples in eight Korean red pine (Pinus densiflora Sieb. et Zucc.) forests. For each forest, CWD samples (diameter: 11.1 ± 0.1 cm; length: 10.2 ± 0.0 cm) from similarly aged Korean red pine trees were laid on the mineral soil surface from May to June, 2016, and soils were sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(51 reference statements)
0
7
1
Order By: Relevance
“…This is a common finding with CWD studies that have underlying soil properties overshadowing the effects of CWD in both natural and reclaimed forests [2,5]. We did, however, find some significant differences due to CWD applications and these responses varied by CWD levels especially in the plant community including both native and non-native species.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…This is a common finding with CWD studies that have underlying soil properties overshadowing the effects of CWD in both natural and reclaimed forests [2,5]. We did, however, find some significant differences due to CWD applications and these responses varied by CWD levels especially in the plant community including both native and non-native species.…”
Section: Discussioncontrasting
confidence: 41%
“…Also, the use of CWD extract in the incubation study rather than CWD fragments on the soil surface as in our field study may have altered nutrient cycling processes. Other studies have also shown lower inorganic N under CWD [2,5] measured using standard extraction procedures in field studies. Our integrative measure of soil nutrient supply using ionic membranes depends on water moving through soil to allow nutrients to absorb to the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of microbial biomass C (MBC) and N (MBN) were determined by the fumigation-extraction method (Brookes et al 1985;Vance et al 1987), as modified by other studies (Kim et al 2017;Perakis and Hedin 2001;Witt et al 2000). Field-moist samples (8 g) were fumigated with alcohol-free chloroform for 24 h at room temperature and atmospheric pressure.…”
Section: Microbial Biomassmentioning
confidence: 99%
“…These trends demonstrated that the response of various microbial biomass ratios to thinning might inconsistently change with the increasing of thinning intensity [36], which was consistent with previous studies. Furthermore, our results may also suggest that the inconsistent changes in microbial stoichiometry characteristics after thinning practice could be attributed to changes in water content, nutrient concentration, and microenvironment [56][57][58]. Moreover, forest thinning has a significant impact on MBC: MBN and MBC: MBP, which might indicate that the accumulation of MBC content in soil is more sensitive to thinning practice than the concentration of MBN and MBP in soil.…”
Section: Variation Of Soil Properties and Stoichiometry Following Thimentioning
confidence: 76%